ELECTROMAGNETIC SCATTERING FROM TWO-DIMENSIONAL COMPOSITE OBJECTS - Kishk, Ahmed A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Different surface integral equations are presented for two- dimensional composite objects. The objects consist of impedance bodies partially coated with dielectric materials. In all of the formulations, the impedance boundary condition is applied on the impedance surface to reduce the matrix size in the numerical solution. The integral equations are reduced to a system of linear equations via the point matching technique. Application of the point matching technique is straight forward for two dimensional objects. Because of this surface discontinuities can be treated easily without the problems encountered when using triangle basis functions as a result, consideration of two-dimensional objects gives a clear picture of the accuracy that can be obtained using these formulations. Two of the formulations discussed herein overcome the problem of internal resonance. The numerical solutions are verified either by comparison with the analytical solutions for cylindrical objects or by applying self consistency tests for targets without analytical solutions. [Vol. 9, No. 1 (1994), pp 32- 39]